A comparative study among different structures of garment sample development - Advincula, Joyce Dianne M. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Garment manufacturing firms nowadays embark on renewing the product development to reduce cost and have a competitive edge in the industry. One way of doing so is by implementing a structural change in the sample development of a garment, which is an organizational rearrangement strategy. This study aimed to determine the effects of employing a garment consultant in the garment sample development to design manufacturability; output consistency with design concept; time delivery cycle; prime cost of production; and working relationship that transpired throughout the process, by means of comparing three simulated garment sample development that utilized the same design: the designer and sample maker worked independently (serial approach); collaboratively (team approach); and mediated with a garment consultant (structural change approach). Results showed that employment of garment consultant is related to production of a more cost effective and design concept-accurate output. However, it turned out that accuracy-to-the-design concept and time delivery cycle had an inverse relationship. With regards to the working relationship of the people involved, it was found that interposing a garment consultant could result to more strains in the interaction of participants. Results also showed that each sample development structure has its own advantages and disadvantages. The researcher recommends garment manufacturing firms to study their existing sample development and apply the structure that best fit their needs. For repeat studies, the researcher recommends the following: 1.) conduct more trials in each structure; 2.) do a more detailed time study; 3.) include a by-operation labor cost computation and; 4.) execute the necessary output revisions.